Stereotype Perempuan dalam Film Yuni - Aldi Mohamad Ridwan; Leadya Raturahmi; Resty Mustika Pratiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Stereotypes of women in society often associate women with domestic roles, virginity, and the value of marriage as a measure of their success in life. This view strengthens patriarchal control which limits women's space in various aspects of life. This research aims to analyze the stereotypical depiction of women in the film